The genus Bactrothrips in China (Thysanoptera: Idolothripinae): morphological and molecular data, and a key with two new species - Dang, Lihong; Qiao, Gexia (Zootaxa, 2012)
Seven species of Bactrothrips Karny are recognized from China, based on morphological and molecular data, including Bactrothrips elongatus n. sp. and B. furvescrus n. sp. Meiothrips baishanzuensis Duan & Li is a new synonym of B. brevitubus Takahashi, and Bactrothrips brevitubus zhamanus Han & Zhang is a new synonym of B. pictipes Haga & Okajima. Molecular evidence provides clear relationships in the N-J tree among species studied here. A generic diagnosis and key to Chinese Bactrothrips species are also given.